Validation of the Indonesian Version of Modified Checklist for Autism in Toddlers: a diagnostic study - Hendra Salim; Soetjiningsih Soetjiningsih; I Gusti Ayu Trisna Windiani; I Gede Raka Widiana; PITIKA ASPR (Paediatrica Indonesiana, 2020)
Background Autism is a developmental disorder for which early detection in toddlers is recommended because of its increased prevalence. The Modified Checklist for Autism in Toddlers (M-CHAT) is an easy-to-interprete tool that can be filled out by parents. It has been translated into the Indonesian language but needs to be validated. Objective To evaluate the diagnostic validity of the Indonesian version of M-CHAT in detection of autism spectrum disorder in Indonesia. Methods A diagnostic study was conducted at Sanglah Hospital, Denpasar, Bali, from March 2011 to August 2013. Pediatric outpatients aged 18 to 48 months were included. The Indonesian version of the M-CHAT tool was filled by parents. Autism assessment was done according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV-TR). The assessment results were analyzed with the MedCalc program software, in several steps: (i) reliability of M-CHAT; (ii) description, distribution, and proportion to determine the characteristics of the subjects of research; and (iii) validity of M-CHAT compared to the gold standard DSM-IV-TR by a receiver operating characteristic curve and several area under the curve cut-off points, in order to assess the sensitivity, specificity, positive predictive value, negative predictive value, and positive and negative likelihood ratio, accompanied by the 95% confidence interval of each value. Results The Indonesian version of M-CHAT in toddlers had 82.35% sensitivity and 89.68% specificity, using the cut-off point of more than 6 failed questions. Conclusion The Indonesian version M-CHAT translated by Soetjiningsih has optimal diagnostic validity for detection of autism in toddlers.